Strengthening Floor Gymnastics Learning to Reduce Anxiety and Enhance Students' Learning Interest - Idah Tresnowati; Gilang Nuari Panggraita; Lukman Alfaris; Larasati; Nurul Aqil Nahari Fasyil (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
Floor gymnastics learning often causes anxiety among students due to fear of injury, lack of self-confidence, and limited mastery of movement techniques. These conditions may lead to low learning interest and suboptimal learning outcomes. This Community Service Program (PkM) aimed to strengthen the learning process of floor gymnastics in order to reduce students' anxiety and enhance their interest in learning through a safe, gradual, and enjoyable instructional approach. The program was conducted on May 8, 2026, at MA Salafiyah Syafi’iyah Proto, Pekalongan Regency, involving students as participants. The implementation methods included the delivery of educational materials on the importance of mental preparedness in floor gymnastics learning, demonstrations of basic techniques, guided step-by-step practice sessions, and continuous motivation and feedback throughout the learning process. The results indicated that the program made a positive contribution to improving students' self-confidence in participating in floor gymnastics activities. Students demonstrated greater willingness to perform each movement, showed higher enthusiasm during the learning activities, and displayed stronger motivation to engage in the learning process. It is expected that this program will create a more conducive learning environment, thereby reducing students' anxiety and increasing their interest in learning floor gymnastics. Furthermore, the program serves as an effort to support student-centered physical education by promoting a balanced development of both physical and psychological aspects.